(untitled) (Journal of Universal Science Research, 2023)
This article focuses on the implementation and benefits of innovative teaching methods in biology classes. It explores various strategies and approaches that educators can employ to enhance student engagement, understanding, and retention of biological concepts. By incorporating innovative teaching methods, instructors can create dynamic and interactive learning environments that cater to diverse learning styles and promote critical thinking skills.